SOSIALISASI DAN PELAKSANAAN ALL STARS KINDERGARTEN SPORTS FESTIVAL - Hatena Manopo, Boyke Adam; Tahki, Kurnia; Dewanti, Rina Ambar; Aryati; Antoni, Rizka (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2023)
Abstract Early age is the age when children begin to recognize themselves and the environment around them, therefore at this time, children must be given various stimuli or stimuli so that their growth and development is good. Early childhood education is a coaching effort aimed at children from birth to 6 years of age which is carried out by giving educational stimuli to help the physical and spiritual growth and development of children in preparation for life and can adapt to their environment and have readiness to enter further education. Age 4-6 years is a mature age for early childhood to maximize movement activity, and physical fitness. Therefore, this service aims to socialize basic movement activities to carry out early childhood sports festival activities with the theme "Socialization and Implementation of All Stars Kindergarten Sports Festival" on January 28, 2023 at the velodrome rawamangun field. The event went smoothly and was followed happily by early childhood children. Abstrak Usia dini merupakan usia dimana anak mulai mengenal diri dan lingkungan di sekitarnya oleh karena itu pada masa ini anak harus diberi berbagai stimulus atau rangsangan agar tumbuh kembangnya menjadi baik. Pendidikan usia dini merupakan suatu upaya pembinaan yang ditujukan kepada anak sejak lahir sampai dengan usia 6 tahun yang dilakukan melalui pemberian rangsangan pendidikan untuk membantu pertumbuhan dan perkembangan jasmani dan rohani anak sebagai persiapan untuk hidup dan dapat menyesuaikan diri dengan lingkungannya serta memiliki kesiapan untuk memasuki pendidikan lebih lanjut. Usia 4-6 tahun merupakan usia matang bagi anak usia dini untuk memaksimalkan aktifitas gerak, dan kebugaran fisiknya. Maka dari itu pengabdian ini bertujuan untuk mensosialisasikan aktifitas gerak dasar melaksanakan kegiatan festival olahraga anak usia dini dengan tema “Sosialisasi dan Pelaksanaan All Stars Kindergarten Sports Festival“ telah pada tanggal 28 Januari 2023 di lapangan velodrome rawamangun. Acara berjalan lancar dan diikuti riang gembira oleh adik adik usia dini.